Perempuan Sebagai Wali Nikah - Fauzi, Moh. (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
The debate on whether or not a wali is required in a marriage contract has been a long standing issue among Muslim jurists, particularly during the formation of madzahib (schools of thought). The mainstream view held by Indonesian Muslims who are mostly adhered to the Syafi'i madzhab is that the presence of a wali becomes a criteria for the validity of a marriage. However, if the issue of wali is being re-examined by using historical and Islamic jurisprudence approach it is found that the presence of wali is not required in all marriage contracts of all women. A woman may become a wali and may marry off herself without a wali if she fulfils the requirement of being a wali, namely intelligent, sound of judgment, mature and independent. Such a view is held by scholars from the Hanafi school of law. Nevertheless, the concept of wali is not merely a legal issue; it is a meant for guaranteeing the wellbeing of a woman upon entering her marriage. The Prophet is therefore suggested that wali should be presented in a marriage contract.